Presentation N° 15 (2025) - Castro, Augusto (2025)
We present issue number 15 of our journal Kawsaypacha: Society and Environment. This edition continues our ongoing effort to compile research related to the social and environmental challenges of our time. The issue is divided into two sections. The first section features the Dossier: Environmental Policy and Management, which has been organized and prepared by Dr. Iván Ortiz. It includes twelve articles dedicated to topics such as environmental policy, environmental control and management, and studies on the environment. The second section, Academic Articles and Essays, contains several additional contributions addressing diverse topics such as watershed management, tourism policies, issues related to the co-production of knowledge, and proposals aimed at improving the planet’s conditions.